2018
DOI: 10.1111/cdev.13070
|View full text |Cite
|
Sign up to set email alerts
|

Intrapersonal Emotion Regulation Processes Influence What Children Remember About Their Emotional Experiences

Abstract: Little work has tested how emotion regulation (ER) processes influence children's memory for negative experiences. We investigated how two intrapersonal ER processes (affect-biased attention and changes in negative feelings) predicted children's (N = 184, 93 girls, ages 3-11) memory. Recall of a sad or scary film was tested after a delay. The way discrete emotional information was remembered varied with ER and children's age. Older children with greater affect-biased attention or less reduction of fear demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Some of the researchers found that emotional appraisal may affect some of the reactions. According to Fernando et al (2017) and Parsafar and Davis (2018), an emotional appraisal is a process by which a variety of reactions are generated as a result of the event's subjective judgements. The term "emotional appraisal" refers to the processes by which individuals' cognitions about events anticipate their emotional reactions to those experiences.…”
Section: Behaviour Changementioning
confidence: 99%
“…Some of the researchers found that emotional appraisal may affect some of the reactions. According to Fernando et al (2017) and Parsafar and Davis (2018), an emotional appraisal is a process by which a variety of reactions are generated as a result of the event's subjective judgements. The term "emotional appraisal" refers to the processes by which individuals' cognitions about events anticipate their emotional reactions to those experiences.…”
Section: Behaviour Changementioning
confidence: 99%
“…The construction of this “emotion theorizing” is closely linked to the emergence of the theory of mind for which a pivotal phase is typically observed from the age of 4. “Emotion theorizing” also appears necessary for the regulation of emotions and, by extension, adaptation in general ( 7 , 8 , 10 12 ). Emotion regulation skills develop more steadily across childhood and adolescence ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not yet clear in what sense the emotional valence of events is associated with memory processing in preschoolers. Emotional appraisal can be defined as the process through which different responses are generated from the same event, based on subjective assessment of events or stimuli (Nieto and Delgado, 2006; Kuppens et al, 2012; Moors, 2013, 2017; Moors and Scherer, 2013; Fernando et al, 2015; Parsafar and Davis, 2018; Scherer and Fontaine, 2018). People constantly perform emotional assessments of events and stimuli according to what it implies for their own well-being, objectives, and concerns (Kuppens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…People constantly perform emotional assessments of events and stimuli according to what it implies for their own well-being, objectives, and concerns (Kuppens et al, 2012). These appraisal responses are considered the closest psychological determinants of emotions (Ellsworth and Scherer, 2003; Kuppens et al, 2012), so these would be one of the results of the assessment (Ellsworth and Scherer, 2003; Parsafar and Davis, 2018).…”
Section: Introductionmentioning
confidence: 99%